Adaptive Strategies in Building Business Resilience Amidst the Dynamics of Management Change - Christin, Mariana; Sondang, Roma (Economy, Business, Finance, Accounting & Management Journal, 2025)
This study explores the implementation of adaptive strategies to build business resilience amid dynamic changes in management. Utilizing a qualitative approach with case study methods, the research examines how organizations respond to internal and external pressures through flexible decision-making, continuous learning, and proactive leadership. The findings reveal that adaptive strategies significantly enhance organizational resilience by enabling businesses to navigate uncertainty, innovate, and maintain competitive advantage. However, challenges such as resource constraints and resistance to change can impede the effectiveness of adaptation efforts. This study contributes both theoretically and practically by providing insights into the integration of adaptive strategies in managing change and sustaining business continuity in volatile environments